Thames Mudlarking : Searching for London's Lost Treasures - Sandy, Jason (Shire Library, 2021)
Cover -- Contents -- Introduction: Mudlarking -- Megalodons, Woolly Rhinos and Flint Tools -- Rituals and Votive Offerings -- Vanity and Sex -- Zoomorphic Art and Viking Attacks -- Pilgrims, Knights and Betrayal -- Opulence and Witchcraft -- War, Fire and Love -- Death and Decadence -- Empire and Invention -- Keep Calm and Carry On -- Eternal River -- Liquid History -- Places to Visit -- Further Reading -- Index -- Imprint.